Il-6 and il-12 cytokines expression in hela cells treated with oroxylum indicum (beko) leaves extract. - Lim, Lim Yee Ying Slyvia (Universiti Sains Malaysia, 2016)
Infection with high-risk group of human papillomavirus (HPV) is strongly associated with cervical cancer development. The prolonged duration of HPV infection is associated with effective evasion of immune surveillance thus delaying the activation of adaptive immunity. Oroxylum indicum (O. indicum) is one of the local edible plants traditionally used for cancer treatment because of its antiproliferative activity on cervical cancer cells. O. indicum was chosen to study their effect on IL-6 and IL-12 cytokines expression in cervical cancer cells, HeLa cells. Leaves of O. indicum were dried and extracted using methanol. The extract was tested on HeLa cells proliferation activity using methylene blue assay (MBA) for the determination of IC50 value. Cisplatin has been used as the positive control. Results showed that O. indicum extract exhibited antiproliferative activity in HeLa cells with IC50 of 8.88pg/ml which is lower than cisplatin. The IC30 value of O. indicum extract was used to determine the effect of plant extract on the expression of IL-6 and IL- 12 in HeLa cells. TNF-a was reported to induce the production of IL-12 and the downstream cytokine of IL-12, IL-6. Therefore, TNF-a was used as a stimulant for cytokines production. HeLa cells were stimulated with and without TNF-a for one hour prior to extract treatment for another 24 hours. The protein production of IL-12 and IL-6 were quantified using enzyme-linked immunosorbent assay (ELISA). The results showed that there were increased IL-12 protein production and decreased IL-6 protein production after O. indicum treatment. The mRNA expressions of both cytokines were evaluated using the reverse transcription polymerase chain reaction (RT-PCR) technique. The results showed that there were decreased in the IL-12 expression on HeLa cells induced by TNF-a after O. indicum treatment. However, the expression of IL-6 mRNA was not detected after TNF-a stimulation and O.indicum treatment. In conclusion, the methanol extract of O. indicum induce the IL-12 cytokines expression, and reduce the production of IL-6.